META-ANALYSIS OF THE EFFECT OF DISCOVERY LEARNING MODEL ON PHYSICS LEARNING OUTCOMES - Ningsih, Allin Wel; Qorinatul Aulia, Nurul Fadilah; Uzfa, Vaizatul; Desnita, Desnita (Journal of Learning and Technology in Physics, 2024)
The purpose of this study is to learn the great impact the discovery learning model has on learning, based on education and lesson materials. The kind of research is a meta-analysis. The subject of this study is 24 scientific articles published by some journals from 2015 to 2020. Research instruments of coding sheets. For the impact of the discovery learning model on high school education, it has a moderate category with the effect size of 0.72 and the ladder junior high school education has high ratings on an effect size of 1.26. the impact of the discovery learning model on lesson materials has a moderate category with an effect size range of 0.67 to 0.80. As for high ratings, it has an effect size of 1.20. In general, the discovery learning model affects the study of physics.Keywords: Meta-analysis, Discovery learning, Learning outcomes